Influence of the surface etching on the corrosion behaviour of a three‐dimensional printed Ti–6Al–4V alloy. Issue 10 (3rd June 2020) - Fojt, Jaroslav; Kacenka, Zdenek; Jablonska, Eva; Hybasek, Vojtech; Pruchova, Eva
Abstract: Recently, there has been an extension of three‐dimensional (3D) printing technology of metal materials in the medical field. Additive technology has made it possible to manufacture customized implants. However, 3D printing products often require surface treatment. The possible treatments include acid etching. This study investigated the effect of surface etching on the corrosion resistance of Ti–6Al–4V alloy concerning biological applications. The samples were etched in a mixture of hydrofluoric acid and nitric acid. The corrosion behaviour was described by measuring the time dependence of polarization resistance in a saline solution and surface analysis. The results showed that etching creates a fluoride‐rich layer on the surface, which negatively affects the corrosion behaviour of the material for up to 24 hr. Cytocompatibility tests showed that the resulting layer does not affect the biocompatibility of the material. Abstract : Products prepared by additive technology often require further surface treatment, in the case of complex shapes, it is not possible to proceed to classical techniques such as machining and turning. A three‐dimensional printed titanium alloy was etched in an acid mixture. Etching has a negative influence on corrosion behaviour in the long term. The corrosion rate is increased for up to 24 hr exposure. The etching did not influence the cytotoxicity.